Cytotoxicty and Dna Fragmentation in Cancer Cell Lines, Hep–2 and Amn–3, Induced by A Novel Maroon Pigment from Mutant Strain of Rugamonas rubra Rr62 - Hassani, Hayfa H (Al-Nahrain Journal of Science, 2018)
The mutant strain of Rugamonas rubra RR62 produces a novel maroon pigment after cultivation in casein-enriched medium for 48h at 30ºC. The pigment was extracted by acidified methanol and subsequently purified by centrifugation. The partial purified compound was identified using UV– spectrometer. The UV– visible spectrum showed a maximum absorption peak at 500nm. This study was conducted to detect the cytotoxic effects of the maroon pigment on two types of cancer cell lines, Hep–2 and AMN–3, using a cell proliferation assay. The growth of Hep–2 and AMN–3 were significantly (P≤0.05) blocked at high concentrations of pigment and after increasing time of exposure; the inhibition rate was 90 and 91%, respectively. Whereas, no toxic effects were observed, on both models of cell lines, at low concentrations. In addition, the maroon pigment induced apoptosis. The high concentrations of pigment (125 and 31.25μg/ml) was significantly (p≤0.05) increased the percentage of fragmented DNA of Hep–2 and AMN–3(78.4% and 75% respectively).